Hemiuridae (Digenea) from marine fishes of the southern Indian Ocean: Dinurinae, Elytrophallinae, Glomericirrinae and Plerurinae - Bray, R. A. (Systematic Parasitology, 1990)
The following species are described, figured and/or recorded from regions of the southern Indian Ocean: Dinurus longisinus from Coryphaena hippurus, Cape Province and Western Australia and immature in Carangoides gymnostethoides, Western Australia; Ectenurus trachuri from Trachurus declivis, Tasmania, Erilepturus tiegsi from Platycephalus endrachtensis, Pomatomus saltator and Arripis georgianus, Western Australia and Sphyraena novaehollandiae, Tasmania; Tubulovesicula angusticauda (with eight new synonyms) from Trachichthodes gerrardi, South Australia and Gymnothorax woodwardi, Saurida undosquamis and Argyrops spinifer, Western Australia; Elytrophalloides oatesi from Meuschenia freycineti and Aldrichetta forsteri, South Australia; Elytrophalloides humerus n. sp. from Trachinotus botla, Natal; Lecithocladium angustiovum (with four new synonyms) from Rastrelliger kanagurta, Natal; Glomericirrus amadai from Hoplostethus atlanticus, Tasmania; Plerurus digitatus (with 17 new synonyms) from Euthynnus affinis, Scomberomorus commerson, Thunnus albacares, Scomberoides commersonianus, Alectis ciliaris, Pomatomus saltator, Saurida undosquamis, Rachycentron canadum, Natal and Lichia amia and Pomatomus saltator, Cape Province and Carangoides gymnostethoides, Western Australia; Synapto-bothrium sp. from Pomatomus saltator, Western Australia.